PENUYULUHAN TENTANG DAMPAK KEHAMILAN PADA REMAJA DI SMA BALA KESELAMATAN PALU - Jumain Jumain; Wahyu, Agustinus Talindong, Parmi (JOURNAL OF COMMUNITY DEDICATION, 2022)
The lack of disclosure by families, both parents and children, has indirectly opened the door wider to adolescents' deviant behavior, especially premarital sex. Unwanted pregnancy (KTD) is an example of one impact of having premarital sex. Adolescent pregnancy under the age of 20 has an impact on increasing the number of maternal deaths that occur in the world and in Indonesia. This community service aims to increase youth knowledge about premarital sex with a total of 55 participants. The results of the evaluation during the activity process were that all participants understood the counseling material. The results of the evaluation during the activity process were that all participants understood the educational material. With this counseling, it is hoped that students will be able to increase their adolescent knowledge about the effects of pregnancy, so that they can prevent and avoid pregnancy.